Effects of the Mediterranean Dietary Pattern on Gestational Diabetes Mellitus and Its Association with Maternal-Fetal Outcomes: A Systematic Review of Clinical Trials - Chagas, Lucas Almeida das; Silva, Ana Vitória Almeida das Chagas; Sousa, Rosângela Maria Lopes; Callado, Gustavo Yano; Araujo Júnior, Edward; Mattar, Rosiane (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
In recent years, the role of healthy dietary patterns—particularly the Mediterranean diet—has been increasingly investigated in the prevention and management of gestational diabetes mellitus (GDM) and its associated complications.To evaluate the effects of adherence to the Mediterranean dietary pattern (MedDiet) adopted prior to conception or early in gestation on GDM and its association with maternal and fetal outcomes.A systematic literature search was conducted, including randomized and non-randomized clinical trials. Data were collected from Biblioteca Virtual em Saúde (BVS), PubMed, Embase, and Google Scholar databases for articles published between 2015 and 2025. The review protocol was registered in PROSPERO under the registration number CRD420251008611. The average incidence of GDM was lower in the MedDiet group (15.2%) compared to the control group (18.5%), suggesting a beneficial effect of the intervention. There was also a reduction in urinary tract infection rates (6.8% vs. 14.9%) and in the incidence of hypertension/preeclampsia (6.9% vs. 9.5%) in the intervention group. Cesarean section rates were similar between groups, with minor variations. Regarding neonatal outcomes, birthweight was slightly higher in the MedDiet group, and the incidence of small-for-gestational-age newborns was lower, reflecting an overall favorable effect on neonatal growth patterns. The rate of preterm birth was also lower in the intervention group, as was perinatal mortality in some studies. The need for neonatal intensive care unit admission varied across studies, with a trend toward reduction in the MedDiet group.The Mediterranean diet appears to be effective in reducing the incidence of GDM and improving maternal and fetal outcomes.
Keywords: Dietary intake; Mediterranean diet; gestational diabetes mellitus; adverse outcomes; pregnancy